Makna dan Tradisi Pukul Manyapu di Negeri Morella Kecamatan Leihitu Kabupaten Maluku Tengah - Renwarin, Nurhayati (ETHNOGRAPHY: Journal of Design, Social Sciences and Humanistic Studies, 2024)
The land of Morella is one of the customary lands found in the Leihitu Peninsula. In this Morella Country, a traditional ceremony has taken place that has been carried out for generations known as "Traditional Ceremony Hit Sweep" or also known as "hit broom sticks" Traditional ceremonies are usually held by the local community to coincide with the 7th day (Shawwal) after the celebration of Eid al-Fitr 1 Shawwal every Hijri Year. This study aims to determine the implementation and traidisi of the time of manyapu in the Morella State Community. The type of research is qualitative descriptive, which is a research process that is carried out to analyze information obtained from the community in the form of words, daily behaviors of the community in the tradition of hitting manyapu. The data collection technique uses observation, interview and literature studies or documentation. The data from this study was analyzed qualitatively. The findings of this study, namely the Hit Manyapu attraction, were carried out as a form of commemoration of the struggle of Kapitan Telukabessy, Ahmad Leikawa, in his struggle against the Netherlands colonizers. As a result of the struggle, several young men from the country of Morella were held captive by the Netherlands for three months. This attraction has been maintained to this day. The values and norms that grow and develop in people's lives are actualized in the form of traditional culture and traditions of Tik Manyapu and preserved from one generation to the next